An overview of autophagy in the differentiation of dental stem cells - ZHAO, XITONG; JU, TIANJUAN; LI, XINWEI; LIU, CHANGFENG; WANG, LULU; WU, LI-AN (Biocell, 2024)
Dental stem cells (DSCs) have attracted significant interest as autologous stem cells since they are easily accessible and give a minimal immune response. These properties and their ability to both maintain self-renewal and undergo multi-lineage differentiation establish them as key players in regenerative medicine. While many regulatory factors determine the differentiation trajectory of DSCs, prior research has predominantly been based on genetic, epigenetic, and molecular aspects. Recent evidence suggests that DSC differentiation can also be influenced by autophagy, a highly conserved cellular process responsible for maintaining cellular and tissue homeostasis under various stress conditions. This comprehensive review endeavors to elucidate the intricate regulatory mechanism and relationship between autophagy and DSC differentiation. To achieve this goal, we dissect the intricacies of autophagy and its mechanisms. Subsequently, we elucidate its pivotal roles in impacting DSC differentiation, including osteo/odontogenic, neurogenic, and angiogenic trajectories. Furthermore, we reveal the regulatory factors that govern autophagy in DSC lineage commitment, including scaffold materials, pharmaceutical cues, and the extrinsic milieu. The implications of this review are far-reaching, underpinning the potential to wield autophagy as a regulatory tool to expedite DSC-directed differentiation and thereby promote the application of DSCs within the realm of regenerative medicine.